Search for chargino-neutralino production in events with Higgs and W bosons using 137 fb-1 of proton-proton collisions at ?s=13 TeV - Tumasyan, A.; Adam, W.; Andrejkovic, J. W.; Bergauer, T.; Chatterjee, S.; Dragicevic, M.; Escalante Del Valle, A. (Springer, 2021)
A search for electroweak production of supersymmetric (SUSY) particles in final states with one lepton, a Higgs boson decaying to a pair of bottom quarks, and large missing transverse momentum is presented. The search uses data from proton-proton collisions at a center-of-mass energy of 13 TeV collected using the CMS detector at the LHC, corresponding to an integrated luminosity of 137 fb(-1). The observed yields are consistent with backgrounds expected from the standard model. The results are interpreted in the context of a simplified SUSY model of chargino-neutralino production, with the chargino decaying to a W boson and the lightest SUSY particle (LSP) and the neutralino decaying to a Higgs boson and the LSP. Charginos and neutralinos with masses up to 820 GeV are excluded at 95% confidence level when the LSP mass is small, and LSPs with mass up to 350 GeV are excluded when the masses of the chargino and neutralino are approximately 700 GeV.
Keywords: Hadron-Hadron scattering (experiments); Supersymmetry; Higgs physics